En Parent–Staff Collaboration in Norwegian Early Childcare Centers - Anne Grethe Sønsthagen; Karin Street (Nordisk Barnehageforskning)
Collaboration between parents and staff in early childcare centers is important because it supports children’s well-being, development, and learning. COVID-19 brought worldwide structural changes to how staff and parents could collaborate. This study examines the impact of COVID-19 on parents’ perceived collaboration with Norwegian early childcare centers before and after the first lockdown in spring 2020. First, we investigated the structural validity of the national Parent Survey conducted in the region Vestland during fall 2019 (n = 8,978). Data from the fall 2019 survey (n = 1,603) and an adapted version during spring 2020 (n = 313) were then used to investigate differences in perceived collaboration. The results support a four-factor solution, including parents’ perceptions of staff–child relationships, information, participation, and interactions. Parents’ perceptions of two factors (information and interactions) were significantly more positive in 2020 than in 2019. This study provides valuable insights into the impact of COVID-19 on collaboration between parents and staff and highlights the influence of organizational structure on parental collaboration.